Kapabilitas Dinamik dan Keunggulan Bersaing: Dinamisme Lingkungan Moderator ataukah Driver? - Khouroh, Umu; Windhyastiti, Irany; Ratnaningsih, Christina Sri; Irany Windhyastiti (Jurnal Samudra Ekonomi dan Bisnis, 2021)
The aim of this study is to investigate the role of environmental dynamism in relation to dynamic capabilities and competitive advantage. This study uses a quantitative approach and type of explanatory research. The survey was conducted at 130 MSMEs in Malang Raya. Hypothesis testing using SEM-PLS. The findings of the study prove that environmental dynamism is a driver for dynamic capability, while providing evidence that environmental dynamism acts as a negative moderator for achieving competitive advantage. Another finding is that dynamic capabilities have a major effect on competitive advantage while simultaneously acting as fully mediating environmental dynamism with competitive advantage. The implication is important for MSMEs to develop dynamic capabilities in order to deal with environmental dynamism so that MSMEs can increase competitive advantage because if they do not develop dynamic capabilities, environmental dynamism will reduce MSME's competitive advantage.